Effect of Corn Cob and Bagasse Composition on The Growth and Production of White Oyster Mushroom (Pleurotus ostreatus): Pengaruh Komposisi Bonggol Jagung dan Ampas Tebu terhadap Pertumbuhan dan Produksi Jamur Tiram Putih (Pleurotus ostreatus) - Sunirma, S; Taskirawati, Ira; Baharuddin, B (PERENNIAL, 2026)
The increasing use of wood sawdust in the particleboard industry has encouraged the search for alternative substrates for white oyster mushroom cultivation. This study evaluated the effect of corn cob and bagasse composition as lignocellulosic growing media for Pleurotus ostreatus. The experiment was arranged in a Completely Randomized Design with four replications. Growth and production variables observed were mycelial colonization time, pinhead formation time, harvesting time, fresh weight, and number of fruiting bodies. The results showed that mixtures of corn cobs and bagasse can be used as alternative substrates for P. ostreatus. Substrate composition significantly affected mycelial colonization time, whereas pinhead formation time, harvesting time, fresh weight, and number of fruiting bodies were not significantly affected. Among the sawdust-free treatments, P5 (200 g corn cob + 600 g bagasse) produced the highest fresh weight (113.16 g), although its production performance was generally comparable to that of the other treatments. These findings indicate that corn cobs and bagasse have potential as sustainable alternative substrates for white oyster mushroom cultivation.